ICNP® terminological subset for people with diabetic foot ulcer in primary health care - Halene Cristina Dias de Armada e Silva; Sonia Acioli; Patricia dos Santos Claro Fuly; Silvia Maria de Sá Basilio Lins; Juliana Otaciana dos Santos; Danielle Lemos Querido; Alessandra Conceição Leite Funchal Camacho; Harlon França de Menezes (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to elaborate an ICNP® terminological subset for people with diabetic foot ulcers in Primary Health Care. Methods: this is a methodological study that followed five steps: 1) Identification of relevant terms for the patients through an integrative literature review and official documents in the area; 2) Mapping of terms identified with ICNP® terms; 3) Construction of statements of nursing diagnoses, outcomes and interventions; 4) Structuring of a terminological subset with the Self-Care Deficit Theory; and 5) Content validity of statements constructed with nurses from a programmatic area in Rio de Janeiro. Results: the subset developed is composed of 81 diagnoses/outcomes and 583 nursing interventions, organized into universal, change and development requirements. Conclusions: the subset on screen was predominantly composed of statements inserted in self-care requirements related to health changes, reinforcing the importance of quality of life and recovery.